The effectiveness of the promotional tools in creating awareness to current and potential clients of Islamic Banking and Finance Institute Malaysia / Noor Nadirah Mohd Adam - Mohd Adam, Noor Nadirah (Faculty of Business and Management, 2008)
This research is about a study of the effectiveness of the promotional tools in creating awareness to current and potential clients of IBFIM. These promotional tools which include direct marketing, advertising, publicity, sales promotion and personal selling are the factors that have been done by IBFIM in creating awareness to current and potential clients. This survey is conducted at Islamic Banking and Finance Institute Malaysia Kuala Lumpur. The sample size for this study is 80 respondents. There were 100 questionnaires being distributed and only 80 were returned and completed. Data obtained using two methods that are primary and secondary data. Respondents are required to answer the questionnaires that contain promotional tools in creating clients awareness. Data are analyzed using Reliability Test, Frequency, Cross Tabulation and T-test through SPSS program. From the results, it was identified that advertising is the most effectiveness of the promotional tools that have been practiced by IBFIM. While advertising, personal selling and direct marketing are significance that will influence clients awareness towards IBFIM.